Aristotle on the apparent good perception, phantasia, thought, and desire - Moss, Jessica Dawn, 1973- (Oxford : Oxford University Press, 2012)
Aristotle holds that we desire things because they appear good to us - a view still dominant in philosophy now. But what is it for something to appear good? This text argues that the notion of the apparent good is crucial to understanding both Aristotle's psychological theory and his ethics.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Aristotle; Moral motivation